2006
DOI: 10.1037/0893-164x.20.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual model for maternal behavior among polydrug cocaine-using mothers: The role of postnatal cocaine use and maternal depression.

Abstract: This study examined the association between maternal cocaine use and maternal behavior and tested a conceptual model predicting maternal insensitivity during mother-infant interactions. Participants included 130 mother-infant dyads (68 cocaine-exposed and 62 noncocaine-exposed) who were recruited after birth and assessed at 4-8 weeks of infant age. Results of model testing indicated that when the effects of prenatal cocaine use were examined in the context of polydrug use, maternal psychopathology, maternal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…At the behavioral level, such motivation can be demonstrated in preclinical models using the same procedures borrowed from the addiction field namely, conditioned place preference (Mattson et al, 2001), operant conditioning bar-pressing procedures (Wilsoncraft, 1968) and choice tasks (Mattson et al, 2001). The association between social attachment and addiction is further supported by extensive clinical literature on poor couple (Ghitza et al, 2007) and parental (Coyer, 2003; Eiden et al, 2006) functioning in individuals afflicted with substance use disorders. Hence, addiction entails taking over motivational and emotional systems by switching evolutionary programmed and normatively sensitized incentive targets (e.g., sexual attractions and maternal care) for the ones bearing absolutely no benefits for an individual.…”
Section: 4 Social Attachment and Addiction: Shared Neurobiology Anmentioning
confidence: 91%
“…At the behavioral level, such motivation can be demonstrated in preclinical models using the same procedures borrowed from the addiction field namely, conditioned place preference (Mattson et al, 2001), operant conditioning bar-pressing procedures (Wilsoncraft, 1968) and choice tasks (Mattson et al, 2001). The association between social attachment and addiction is further supported by extensive clinical literature on poor couple (Ghitza et al, 2007) and parental (Coyer, 2003; Eiden et al, 2006) functioning in individuals afflicted with substance use disorders. Hence, addiction entails taking over motivational and emotional systems by switching evolutionary programmed and normatively sensitized incentive targets (e.g., sexual attractions and maternal care) for the ones bearing absolutely no benefits for an individual.…”
Section: 4 Social Attachment and Addiction: Shared Neurobiology Anmentioning
confidence: 91%
“…In an intervention study, Schuler et al 11 found that ongoing maternal cocaine and/or heroin use and rigid parenting attitudes predicted decreased maternal competence during mother-child play interactions at 18 months postpartum. In another study, Eiden et al 1 revealed that continued cocaine use postpartum among mothers with depression and/or anxiety was a significant predictor of greater maternal insensitivity and negative parenting behaviors during feeding interactions with their 4- to 6-week old infants.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers who use cocaine while pregnant have a tendency to abuse additional substances including alcohol, marijuana, and tobacco, 1 and many continue to use drugs after delivery. These mothers typically reside in high-risk environments characterized by low-income communities, inadequate nutrition, ongoing familial substance use, homelessness and minimal social support.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations